A review on synthesis, characterization, and pharmacological evaluation of second-line antidiabetic drugs - Islam, Mafuza (Brac University, 2024)
This thesis submitted to the School of Pharmacy in partial fulfillment of the requirements for the degree of Bachelor of Pharmacy, 2023.